DESAIN LABORATORIUM VIRTUAL BERBASIS IJEN GEOPARK PADA MATERI IPA DI SMP SEBAGAI MEDIA PEMBELAJARAN INTERAKTIF - Praditya Tri Revanza; Zainur Rasyid Ridlo; Vendwina Saphire Rizqi (saintifika, 2022)
The virtual laboratory is an IT-based learning media. The purpose of this study was to develop a virtual laboratory design to increasing conceptual understanding of science material at the junior high school level on science material with topics of physics, chemistry, biology, and earth sciences. This virtual laboratory was developed as a form of utilizing technology in the field of education, where the development of information technology is currently very supportive of implementing practical simulations in a virtual laboratory. The research method of this research applies the Research and Development (R&D) method with 3D steps. The development steps include: identification, design, and development. Validation stage of media experts, material experts and media users to assess the feasibility of the media and test development to see the effectiveness of using media in learning as well as student responses to the effectiveness of learning by using virtual laboratory media.